Effect of Green Fertilizer of Gamal Plant (Gliricidia sepium (Jacq) DC.) On the Growth of Duku (Lansium domesticum Corr.) - Eryani (Talenta Publisher, 2020)
Duku is one of the fruits favored by the people of Indonesia. Jambi Province produces duku kumpeh (Lansium domesticum Corr.) Which is known as a national superior product. One obstacle in the development of duku kumpeh by farmers in Jambi is the conventional pattern of cultivation, so product availability is not continuous, because farmers only look after old gardens. One of the efforts to increase and accelerate the growth of duku is by giving green fertilizer. One type of green fertilizer is green fertilizer derived from Gamal plants (Gliricidia sepium (Jacq) Dc.). Gamal contains nutrients, namely: 3.7% nitrogen, 0.2% phosphorus, 2.2% potassium, 3.2% calcium, and 0.8% magnesium. The purpose of this study was to determine the effect of applying gamal green fertilizer on the growth of duku kumpeh. The study used a Completely Randomized Design (CRD) with 5 levels of fertilizer treatment namely 0 g, 6.5 g, 13 g, 26 g, and 52 g. Each treatment was repeated 5 times. The parameters observed were height increase, number of leaves, leaf area, wet weight, and dry weight of plants. The data obtained were analyzed through Analysis of Variance (Anova), and post hoc Duncan Multiple Range Test (DNMRT) at 5% significance level. The results showed that the dose of gamal green green fertilizer affected the growth of plant height, but did not affect the number of leaves, leaf area, wet weight and dry weight of the plant